Psycholinguistic Aspects of Reproducing the Chinese Military and Political Discourse in Ukrainian - Tetiana Korolova; Oleksandra Popova (Психолінгвістика)
The article is aimed at studying psycholinguistic issues regarding the interpretation variability and linguocultural accommodation of conceptual basis representing the determinants of the Chinese military and political discourse by the Ukrainians. The topicality is stipulated by great interest of the scientists in the fields of psycholinguistics, linguistic culturology, translation studies as to the semantic content within the view of the world displayed by ethnic groups from The Orient. The determinants of the Chinese military and political discourse (discourse, concept, concept sphere, linguistic component, extra-linguistic component) are specified in the article. The Chinese-language military-political discourse is understood as a totality of verbalized oral and written texts created in the context of the politics-oriented communication; ideographic and symbolic embodiment of the national concept sphere, which is governed by the national and culture-centric tactical and strategic vectors of the conflict-free interaction performed by communicants in the spheres of politics, economy, military-industry, international relations. The linguistic phenomena enable the Chinese military and political discourse to be actualized as well as the means of their reproduction in the Ukrainian language [replication (equivalent translation), transliteration, transcoding, descriptive translation, commentary; the communication-equal translation strategy; the redirection strategy where cultural and linguistic adaptations are applied]. The prospects of our further research are seen in the study of tactical and strategic vectors which may determine the peculiarities of reproducing the syntactic component of the discourse under study into the Ukrainian language.